Examining the transfer of male DNA onto female underwear in simulated non sexual social interaction versus digital penetration to assist in the evaluation of results in casework scenarios. Issue 1 (January 2023) - Doole, Sharon; Hargreaves, Charlotte; Davidson, Geraldine; Alexander, Karen; Boyce, Maggie; Fraser, Isla; Murphy, Charlotte; Lee-Gorman, Marce; Rogers, Carol
Highlights: Simulated sexual assaults to investigate transfer of male DNA to female underwear. Y-STR analysis carried out on samples taken from inside female underwear. Low expectation of Y-STR profile with statistical evaluation through social contact. Y-STR profile with statistical evaluation can be obtained from co-habiting male(s) Traces of male DNA can be found even if no co-habiting male or sexual activity. Abstract: Experiments have been carried out by the UK and Ireland Association of Forensic Science Providers Body Fluid Forum (AFSP BFF) to determine the levels of male DNA, detected during Y-STR analysis, that may be expected on female underwear from non-sexual social interaction and digital penetration, versus non-sexual social interaction only. The data obtained strongly supports the existing assumptions made: whilst low levels of DNA may be inadvertently transferred to the inside surface of a female's underwear during social interaction with a male, there is a low expectation of detecting a matching Y-STR profile to that male, which is suitable for statistical evaluation, unless he is a co-habitant of that female.